Integrated reporting practices among real property listed companies in Malaysia / Jauharoh Jamal and Erlane K Ghani - Jamal, Jauharoh; Ghani, Erlane K (Universiti Teknologi MARA Cawangan Selangor, 2016)
Integrated reporting promotes a cohesive and efficient approach to corporate reporting that draws on different reporting strands and communicates a full range of factors that can affect the ability of a company in creating its value over time and enhancing governance at the same time. However, there is a lack of study that has examined integrated reporting practices particularly in a developing country such as Malaysia. This study examines the extent of integrated reporting practices among real property listed companies in Malaysia. This study adopts content analysis on 189 annual reports from 63 real property companies that are listed in Bursa Malaysia. The results show that the real property companies in Malaysia have yet to achieve a satisfactory level of integrated reporting practices. This is because all of the companies have a compliant level of integrated reporting ranging from non-compliance to moderate compliance only. The results also show that the size of the company plays an important role on the extent of integrated reporting practices. The findings in this study provide knowledge to interested parties such as practitioners and academics on the level of integrated reporting practices among public listed companies in Malaysia. In addition, the findings provide ideas to the regulatory bodies to strategise ways in promoting integrated reporting among public listed companies.